1963
DOI: 10.1111/j.2042-7158.1963.tb12811.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Blood and Other Tissue Concentrations of Paracetamol in Dog and Man

Abstract: The even distribution of non-conjugated paracetamol in the tissue waters of the dog has been confirmed. The mean tissue water: plasma water concentration is 1.1. A technique for the determination of non-conjugated paracetamol in man has been devised from existing methods. It has increased sensitivity and is applicable to the routine determination of a large number of samples. This method determines only non-conjugated paracetamol, the sulphated and glucuronated conjugates do not interfere with its accuracy, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1966
1966
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Levels were estimated as total p-aminophenol and were considerably in excess of those found with therapeutic dosage. The range of levels quoted by Gwilt et al (1963) is from 0.45 to 2.6 mg./100 ml. 45 minutes after the ingestion of 1 g. of paracetamol.…”
Section: Discussionmentioning
confidence: 95%
“…Levels were estimated as total p-aminophenol and were considerably in excess of those found with therapeutic dosage. The range of levels quoted by Gwilt et al (1963) is from 0.45 to 2.6 mg./100 ml. 45 minutes after the ingestion of 1 g. of paracetamol.…”
Section: Discussionmentioning
confidence: 95%
“…Barnes and Paget (1965) have reviewed evidence on the series of events leading to hepatic necrosis by drugs which accumulate in the liver. The fact that paracetamol in large but not lethal doses tends to accumulate in liver tissue water (Smith, 1958;Gwilt, Robertson & McChesney, 1963) might have indicated that liver necrosis should be looked for in animals given lethal doses. Actually what prompted us to look for liver necrosis was recent experience in this laboratory with liver necrosis produced by oral administration of tannic acid (Boyd, Bereczky & Godi, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…§Results from two studies. plasma flow rate was used for this calculation because acetaminophen is equally distributed between erythrocytes and plasma 5 and is presumed to equilibrate rapidly between these two phases.…”
Section: Methodsmentioning
confidence: 99%